Vladimir Nabokov and the art of play - Karshan, Thomas (Oxford : Oxford University Press, 2011)
In a 1925 speech, Nabokov declared that 'everything in the world plays', including 'love, nature, the arts and domestic puns.' Thomas Karshan draws on early writings and archival material to argue that play is Nabokov's signature theme, and that his novels form one of the most sophisticated treatments of play ever achieved.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Nabokov, Vladimir Vladimirovich, -- 1899-1977 -- Criticism and interpretation; Play in literature; Literature